A kind of high elastic rubber and preparation method thereof

By adding thermoplastic starch granules and starch to the high-elastic rubber system to coat the modified white carbon black, and combining with plasticizer, the problem of insufficient mechanical strength and processing performance of traditional high-elastic rubber is solved, and a comprehensive improvement of high tensile strength, good processing performance and high anti-aging performance is achieved.

CN118812931BActive Publication Date: 2025-02-28FOSHAN MANQIANG NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411013109.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-02-28
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

When traditional high-elastic rubber improves elasticity, it is difficult to maintain high strength and good processing properties at the same time, resulting in a decrease in mechanical strength and toughness.

Method used

By adding thermoplastic starch granules and starch to a rubber system supplemented by butadiene rubber, modified white carbon black is improved by combining plasticizers.

Benefits of technology

While maintaining high resilience, it greatly improves the tensile strength and anti-aging properties of vulcanized rubber, improves the processing performance of the mixed rubber, and overcomes the shortcomings of poor adhesion and poor agglomeration of butadiene rubber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004964956420000091
    Figure BDA0004964956420000091
Patent Text Reader

Abstract

The invention discloses a high elastic rubber and a preparation method thereof, and relates to the technical field of rubber products. A high elastic rubber, its raw materials include 15-30 parts of natural rubber, 45-50 parts of cis-1,4-di-butadiene rubber, 25-35 parts of solution polymerized styrene-butadiene rubber, 5-10 parts of thermoplastic starch particles, 35-40 parts of starch-coated modified white carbon black, 10-12 parts of plasticizers and other rubber vulcanization aids. By adding thermoplastic starch particles and starch-coated modified white carbon black to a rubber system mainly based on cis-1,4-di-butadiene rubber and supplemented by natural rubber and solution polymerized styrene-butadiene rubber, it is beneficial to keep the vulcanized rubber of the system with high resilience, greatly improve the tensile strength and anti-aging performance of the vulcanized rubber, so that the vulcanized rubber of the system has better comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special rubber, in particular to a high-elastic rubber and a preparation method thereof. Background Art

[0002] Since rubber has good elasticity at room temperature, which other materials do not have, with the development of science and technology, rubber products are gradually being widely used in people's daily lives, such as car tires, sealing pads, racket rubber, rubber shoes or rubber gloves, etc. Elasticity is one of the characteristics of rubber, so rubber is often used in some application fields that require elastic sealing or telescopic rebound, and in some special application fields that require high buffering, there are further requirements for the elasticity of rubber, and high-elastic rubber is also developed.

[0003] Generally, high-elastic rubber will use a compound of natural rubber and cis-1, a rubber with better elasticity, as the base material. In order to further improve the elasticity of the rubber, the staff will often increase the proportion of cis-1, a rubber in the base material in the formula. However, when the proportion of cis-1, a rubber is too large, it will not only directly affect the processing performance of the elastic rubber, resulting in poor colloid adhesion and poor agglomeration, and the problem of crushing during mixing, but also further reduce the mechanical strength and toughness of the elastic rubber product. Traditional formulas are difficult to meet the technical requirements of high elasticity and high strength of rubber products. Therefore, it is of great significance to improve the processing performance and mechanical strength of the rubber while making it highly elastic through improvements in the formula. Summary of the invention

[0004] In order to further improve the processing performance and mechanical strength of high-elastic rubber and improve the comprehensive performance of elastic rubber, the present application provides a high-elastic rubber and a preparation method thereof.

[0005] In the first aspect, the present application provides a highly elastic rubber and a preparation method thereof using the following technical solutions:

[0006] A high elastic rubber and a preparation method thereof, comprising the following raw materials in parts by weight:

[0007] Natural rubber: 15-30 parts;

[0008] Butadiene rubber: 45-50 parts;

[0009] Solution polymerized styrene butadiene rubber: 25-35 parts;

[0010] Thermoplastic starch granules: 5-10 parts;

[0011] Starch coated modified white carbon black: 35-40 parts;

[0012] Stearic acid: 2-3 parts;

[0013] Zinc oxide: 3-5 parts;

[0014] Plasticizer: 10-12 parts;

[0015] Vulcanization accelerator: 2.8-3.2 parts;

[0016] Sulfur: 0.2-0.5 parts;

[0017] Dicumyl peroxide: 0.8-1.2 parts;

[0018] Carbon black: 3-5 parts;

[0019] Silane coupling agent Si75: 4-6 parts;

[0020] Anti-aging agent: 2.8-3.6 parts.

[0021] By adopting the above technical scheme, by adding thermoplastic starch particles and starch-coated modified white carbon black to the rubber system mainly composed of cis-1,4-dimethyl-1-butadiene rubber and supplemented by natural rubber and styrene-butadiene rubber, it is beneficial to maintain the high resilience of the vulcanized rubber while greatly improving the tensile strength and anti-aging performance of the vulcanized rubber, so as to make the mechanical properties of the vulcanized rubber better. In addition, in combination with plasticizers, thermoplastic starch particles and starch-coated modified white carbon black can also effectively improve the Mooney viscosity of the mixed rubber, overcome the shortcomings of poor adhesion, poor agglomeration and low processing performance of cis-1,4-dimethyl-1-butadiene rubber, and help the mixed rubber to fully stick to the roller during the mixing process, thereby improving the processing performance of the mixed rubber.

[0022] Optionally, the method for preparing the thermoplastic starch granules comprises the following steps:

[0023] Corn starch and water are stirred and mixed in a weight ratio of 1: (1-1.5), and then a composite plasticizer composed of formamide, sorbitol and urea is added, wherein the mixing weight ratio of the corn starch to the composite plasticizer is 1: (0.2-0.25), and the mixture is kept at room temperature and fully stirred at a speed of 2500-3000 r / min, and then allowed to stand for 24-48 hours, and then heated, melted, extruded, cooled, granulated, and fully crushed and ground to obtain thermoplastic starch particles.

[0024] By adopting the above technical scheme, corn starch is modified by using a composite plasticizer made of a mixture of formamide, sorbitol and urea, and corn starch can be modified into a thermoplastic starch, thereby effectively improving the melting point of the modified starch particles and imparting a certain thermoplasticity, which is not only conducive to making the thermoplastic starch particles suitable for use in a vulcanized rubber system mainly composed of butadiene rubber, but also can be used as a reinforcing filler to improve the mechanical strength of the vulcanized rubber.

[0025] Optionally, in the composite plasticizer, the mixing weight ratio of the formamide, the sorbitol and the urea is 1:(1-1.2):(0.8-1.2).

[0026] By adopting the above technical scheme, when the mixing weight ratio of formamide, sorbitol and urea is within the range of 1:(1-1.2):(0.8-1.2), the composite plasticizer can fully plasticize and modify the corn starch, thereby facilitating the acquisition of thermoplastic starch particles suitable for use in rubber systems.

[0027] Optionally, the method for preparing the starch-coated modified silica comprises the following steps:

[0028] First, corn starch and water are fully stirred in a weight ratio of 1: (8-10), and the mixture is heated to 62-65° C. and stirred for 2-3 hours. After forming a paste, fumed silica is added, wherein the mixing weight ratio of the silica to the corn starch is 1: (0.15-0.2), heated to 84-86° C. and stirred for 1-2 hours, and then the moisture is dried and fully crushed to obtain starch-coated modified silica.

[0029] By adopting the above technical scheme, the surface of fumed silica is coated and modified with corn starch, and the hydroxyl and aldehyde groups on the starch surface can react and cross-link with the silane groups on the silica surface to form a starch-based covering layer on the silica surface, which is not only beneficial to improve the overall thermal resistance of silica and the thermal stability of the vulcanized rubber, but also the starch can improve the compatibility of silica in the non-polar rubber system, so that it can be evenly distributed in the rubber mixture and fully combined with the rubber system, which is beneficial to further improve the mechanical strength of the vulcanized rubber.

[0030] Optionally, the plasticizer includes a mixture of at least two of coumarone resin, hydrogenated petroleum, hydrogenated rosin, aromatic oil and tall oil.

[0031] By adopting the above technical solution and adding plasticizers such as coumarone resin, hydrogenated petroleum, hydrogenated rosin, aromatic oil and tall oil, not only the overall viscosity of the rubber mix can be improved, making the rubber mix easier to process and shape, but the plasticizer can also appropriately adjust the overall hardness of the vulcanized rubber, so that the high elasticity of the vulcanized rubber can be fully characterized.

[0032] Optionally, the plasticizer is a mixture of the coumarone resin, the hydrogenated rosin and the tall oil, and the mixing weight ratio of the coumarone resin, the hydrogenated rosin and the tall oil is 1:(0.9-1.2):(0.2-0.5).

[0033] By adopting the above technical scheme, when the plasticizer is a mixture of coumarone resin, hydrogenated rosin and tall oil, the prepared vulcanized rubber has good resilience and processing performance, as well as certain mechanical strength, which is beneficial to improving the comprehensive performance of the vulcanized rubber.

[0034] Optionally, the vulcanization accelerator comprises a mixture of N-cyclohexyl-2-benzothiazole sulfenamide and N,N'-dithiocaprolactam, and the mixing weight ratio of the N-cyclohexyl-2-benzothiazole sulfenamide and the N,N'-dithiocaprolactam is 1:(0.4-0.6).

[0035] By adopting the above technical scheme, N-cyclohexyl-2-benzothiazole sulfonamide and N,N'-dithiocaprolactam are mixed and compounded for use, which can effectively improve the vulcanization efficiency of the rubber system in this application, which is mainly composed of butadiene rubber and supplemented by natural rubber and styrene-butadiene rubber, and is beneficial to improving the mechanical properties and heat aging resistance of the vulcanized rubber.

[0036] Optionally, the antioxidant includes one or a combination of antioxidant BLE and antioxidant 4020.

[0037] By adopting the above technical scheme, antioxidant BLE and antioxidant 4020 can be applied to the rubber system mainly composed of butadiene rubber, and both have a certain effect of resisting aging caused by factors such as heat, oxygen, ozone and flexure, and can effectively improve the heat aging resistance of vulcanized rubber.

[0038] Optionally, the antioxidant is a mixture of the antioxidant BLE and the antioxidant 4020, and the mixing weight ratio of the antioxidant RD to the antioxidant 4020 is 1:(2-2.5).

[0039] By adopting the above technical scheme, since the main effects and action mechanisms of antioxidant BLE and antioxidant 4020 are different, when antioxidant BLE and antioxidant 4020 are mixed and compounded with each other, a certain synergistic effect can be produced between antioxidant BLE and antioxidant 4020, which is not only beneficial to further improve the aging properties of the vulcanized rubber such as heat resistance, oxygen, ozone and flexural resistance, but also beneficial to prevent fatigue degradation of the vulcanized rubber and provide better anti-aging protection.

[0040] In a second aspect, the present application provides a method for preparing a highly elastic rubber using the following technical solution:

[0041] A method for preparing high elastic rubber comprises the following steps:

[0042] S1, firstly, the solution polymerized styrene-butadiene rubber is placed alone at 86-92° C. for kneading for 2-3 minutes, then the thermoplastic starch particles and the starch-coated modified white carbon black are added, and the kneading is continued for 2-3 minutes before the rubber is discharged to obtain a first rubber compound;

[0043] S2, placing the natural rubber and the butadiene rubber at 138-145° C. for banburying for 2-3 min, then adding the zinc oxide, the stearic acid, the silane coupling agent Si75, the carbon black and 50% of the first rubber material, and continuing banburying for 2-3 min, then adding the plasticizer, the antioxidant and the remaining first rubber material again, and continuing banburying for 2-3 min to obtain a second rubber material;

[0044] S3, heating the second rubber material to 150-160° C., and adding the vulcanization accelerator, the sulfur and the dicumyl peroxide at the same time, and continuing to mix for 15-20 minutes. After the rubber is discharged, the rubber is pressed into sheets and cooled to obtain a high elastic rubber.

[0045] By adopting the above technical solution, mixing is carried out in batches, which is conducive to fully mixing the rubber and each additive. The thermoplastic starch particles and starch-coated modified white carbon black are first mixed with the solution-polymerized styrene-butadiene rubber, and the two polar fillers can be fully mixed and coated by the solution-polymerized styrene-butadiene rubber, so that they can be fully mixed and dispersed with non-polar natural rubber and cis-butadiene rubber during the second banburying, which is conducive to improving the dispersibility of thermoplastic starch particles and starch-coated modified white carbon black in the rubber system of this application, and fully play a reinforcing role. Secondly, the preparation method is simple and convenient, which is conducive to subsequent mass production.

[0046] In summary, the technical solution of this application has at least one of the following beneficial effects:

[0047] 1. By adding thermoplastic starch particles and starch-coated modified silica to a rubber system mainly composed of butadiene rubber and supplemented by natural rubber and styrene-butadiene rubber, it is beneficial to greatly improve the tensile strength and anti-aging performance of the vulcanized rubber while maintaining the high resilience of the vulcanized rubber, thereby improving the mechanical properties of the vulcanized rubber.

[0048] 2. Through the cooperation between thermoplastic starch particles, starch-coated modified silica and plasticizer, the shortcomings of butadiene rubber, such as poor adhesion, poor agglomeration and low processing performance, can be effectively overcome, which is beneficial to improve the Mooney viscosity of the mixed rubber, make the mixed rubber fully stick to the roller during the mixing process, and improve the processing performance of the mixed rubber. DETAILED DESCRIPTION

[0049] The natural rubber was purchased from Xishuangbanna Jingyang Rubber Co., Ltd., and the specific grade was NR SCR5.

[0050] Butadiene rubber was purchased from Beijing Yanshan Branch of Sinopec, with the specific brand number being BR9000.

[0051] The solution polymerized styrene butadiene rubber was purchased from Beijing Yanshan Branch of Sinopec, and the specific grade was SSBR2506.

[0052] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0053] Preparation Example

[0054] [Preparation Example 1-1]

[0055] A thermoplastic starch is prepared by the following preparation method:

[0056] 10 kg of corn starch and 10 kg of water were fully stirred and mixed, and then a composite plasticizer consisting of 0.625 kg of formamide, 0.625 kg of sorbitol and 0.75 kg of urea was added, and the mixture was fully stirred at a speed of 3000 r / min at room temperature, and then allowed to stand for 48 hours. The mixture was then heated, melted, extruded, cooled, granulated, and fully crushed and ground until the particle size was about 100 μm, to obtain thermoplastic starch particles.

[0057] [Preparation Example 1-2]

[0058] A thermoplastic starch is prepared by the following preparation method:

[0059] 10 kg of corn starch and 15 kg of water were fully stirred and mixed, and then a composite plasticizer consisting of 0.83 kg of formamide, 1 kg of sorbitol and 0.67 kg of urea was added, and the mixture was fully stirred at a speed of 2500 r / min at room temperature, and then allowed to stand for 24 hours. The mixture was then heated and melted, extruded, cooled, granulated, and fully crushed and ground until the particle size was about 100 μm, to obtain thermoplastic starch particles.

[0060] [Preparation Example 2-1]

[0061] A starch-coated modified white carbon black is prepared by the following preparation method:

[0062] First, 6 kg of corn starch and 60 kg of water are fully stirred and mixed, and the temperature is raised to 65 ° C and stirred for 2 hours. After forming a paste, 40 kg of fumed silica is added, heated to 86 ° C and stirred for 1 hour, and then placed in an environment of 110 ° C to dry the moisture, and fully crushed and ground until the particle size is about 100 μm to obtain starch-coated modified silica.

[0063] [Preparation Example 2-2]

[0064] A starch-coated modified white carbon black is prepared by the following preparation method:

[0065] First, 8 kg of corn starch and 64 kg of water are fully stirred and mixed, and the temperature is raised to 62 ° C and stirred for 3 hours. After forming a paste, 40 kg of fumed silica is added, heated to 84 ° C and stirred for 2 hours, and then placed in an environment of 110 ° C to dry the moisture, and fully crushed and ground until the particle size is about 100 μm to obtain starch-coated modified silica.

[0066] Example

[0067] [Example 1]

[0068] A high-elastic rubber comprises the following raw materials: 15kg natural rubber, 50kg cis-1,4-butadiene rubber, 35kg solution-polymerized styrene-butadiene rubber, 10kg thermoplastic starch granules, 35kg starch-coated modified white carbon black, 2kg stearic acid, 5kg zinc oxide, 12kg plasticizer, 2.8kg vulcanization accelerator, 0.2kg sulfur, 1.2kg diisopropylbenzene peroxide, 3kg carbon black, 4kg silane coupling agent Si75, and 3.6kg antioxidant 4020.

[0069] Among them, the thermoplastic starch particles are selected from the thermoplastic starch particles prepared in [Preparation Example 1-1]; the starch-coated modified silica is selected from the starch-coated modified silica prepared in [Preparation Example 2-1].

[0070] The plasticizer includes a mixture of coumarone resin and hydrogenated petroleum. Specifically, in this embodiment, the mixing weight ratio of coumarone resin and hydrogenated petroleum is 1:1.4, that is, the added amount of coumarone resin is 5 kg, and the added amount of hydrogenated petroleum is 7 kg.

[0071] Among them, the vulcanization accelerator includes N-cyclohexyl-2-benzothiazole sulfenamide and N, N'-dithiocaprolactam. Specifically, in this embodiment, the mixing weight ratio of N-cyclohexyl-2-benzothiazole sulfenamide and N, N'-dithiocaprolactam is 1:0.4, that is, the addition amount of N-cyclohexyl-2-benzothiazole sulfenamide is 2kg, and the addition amount of N, N'-dithiocaprolactam is 0.8kg.

[0072] A method for preparing high elastic rubber comprises the following steps:

[0073] S1, firstly, the solution polymerized styrene-butadiene rubber is placed alone at 92° C. for 2 min, then thermoplastic starch and starch-coated modified silica are added, and the mixing is continued for 2 min and then the rubber is discharged to obtain the first rubber compound;

[0074] S2, placing the natural rubber and the butadiene rubber at 145° C. for 2 min, then adding zinc oxide, stearic acid, silane coupling agent Si75, carbon black and 50% of the first rubber material, continuing to banbury for 2 min, then adding the plasticizer, antioxidant and the remaining first rubber material again, continuing to banbury for 2 min, to obtain the second rubber material;

[0075] S3. Heat the second rubber material to 160°C, and add N-cyclohexyl-2-benzothiazolesulfonamide, sulfur and diisopropylbenzene peroxide at the same time, continue mixing for 15 minutes, press and cool after the rubber is discharged, and obtain a high elastic rubber.

[0076] [Example 2]

[0077] A high-elastic rubber comprises the following raw materials: 30kg natural rubber, 45kg cis-1,4-butadiene rubber, 25kg solution-polymerized styrene-butadiene rubber, 5kg thermoplastic starch granules, 40kg starch-coated modified white carbon black, 3kg stearic acid, 3kg zinc oxide, 10kg plasticizer, 3.2kg vulcanization accelerator, 0.5kg sulfur, 0.8kg diisopropylbenzene peroxide, 5kg carbon black, 6kg silane coupling agent Si75, and 2.8kg antioxidant.

[0078] Among them, the thermoplastic starch particles are selected from the thermoplastic starch particles prepared in [Preparation Example 1-2]; the starch-coated modified silica is selected from the starch-coated modified silica prepared in [Preparation Example 2-2].

[0079] Among them, the plasticizer includes a mixture of coumarone resin, hydrogenated rosin and tall oil. Specifically, in this embodiment, the mixing weight ratio of coumarone resin, hydrogenated rosin and tall oil is 1:0.9:0.5, that is, the addition amount of coumarone resin is 4.17 kg, the addition amount of hydrogenated rosin is 3.75 kg, and the addition amount of liquid rosin is 2.08 kg.

[0080] Among them, the vulcanization accelerator includes N-cyclohexyl-2-benzothiazole sulfenamide and N, N'-dithiocaprolactam. Specifically, in this embodiment, the mixing weight ratio of N-cyclohexyl-2-benzothiazole sulfenamide and N, N'-dithiocaprolactam is 1:0.6, that is, the addition amount of N-cyclohexyl-2-benzothiazole sulfenamide is 2 kg, and the addition amount of N, N'-dithiocaprolactam is 1.2 kg.

[0081] Among them, the antioxidant includes a mixed compound of antioxidant BLE and antioxidant 4020. Specifically, in this embodiment, the mixing weight ratio of antioxidant BLE and antioxidant 4020 is 1:2.5, that is, the added amount of antioxidant BLE is 0.8kg, and the added amount of antioxidant 4020 is 2kg.

[0082] A method for preparing high elastic rubber comprises the following steps:

[0083] S1, firstly, the solution polymerized styrene-butadiene rubber is placed alone at 86° C. for 3 min, then thermoplastic starch and starch-coated modified silica are added, and the mixing is continued for 3 min, and then the rubber is discharged to obtain the first rubber compound;

[0084] S2, placing the natural rubber and the butadiene rubber at 138° C. for 3 min, then adding zinc oxide, stearic acid, silane coupling agent Si75, carbon black and 50% of the first rubber material, continuing to banbury for 3 min, then adding the plasticizer, antioxidant and the remaining first rubber material again, continuing to banbury for 3 min, to obtain the second rubber material;

[0085] S3. Heat the second rubber material to 150°C, and add vulcanization accelerator, sulfur and dicumyl peroxide at the same time, continue mixing for 20 minutes, press and cool after rubber removal, and obtain a high elastic rubber.

[0086] [Example 3]

[0087] A high elastic rubber, which differs from [Example 1] in that the added amounts of thermoplastic starch particles and starch-coated modified silica are different.

[0088] In this embodiment, the added amount of thermoplastic starch particles is 5 kg, and the added amount of starch-coated modified silica is 40 kg.

[0089] [Example 4]

[0090] A highly elastic rubber, which differs from [Example 3] in that the plasticizer is different.

[0091] In this embodiment, the plasticizer includes a mixture of coumarone resin, hydrogenated petroleum and aromatic oil. Specifically, in this embodiment, the mixing weight ratio of coumarone resin, hydrogenated petroleum and aromatic oil is 1:1.2:0.2, that is, the addition amount of coumarone resin is 5kg, the addition amount of hydrogenated petroleum is 6kg, and the addition amount of aromatic oil is 1kg.

[0092] [Example 5]

[0093] A highly elastic rubber, which differs from [Example 3] in that the plasticizer is different.

[0094] In this embodiment, the plasticizer includes a mixture of coumarone resin and hydrogenated rosin. Specifically, in this embodiment, the weight ratio of coumarone resin to hydrogenated rosin is 1:1.4, that is, the addition amount of coumarone resin is 5 kg, and the addition amount of hydrogenated rosin is 7 kg.

[0095] [Example 6]

[0096] A highly elastic rubber, which differs from [Example 3] in that the plasticizer is different.

[0097] In this embodiment, the plasticizer includes a mixture of coumarone resin, hydrogenated rosin and tall oil. Specifically, in this embodiment, the weight ratio of coumarone resin, hydrogenated rosin and tall oil is 1:1.2:0.2, that is, the addition amount of coumarone resin is 5 kg, the addition amount of hydrogenated rosin is 6 kg, and the addition amount of tall oil is 1 kg.

[0098] [Example 7]

[0099] A highly elastic rubber, which differs from [Example 6] in that the plasticizer is different.

[0100] In this embodiment, the plasticizer includes a mixture of coumarone resin, hydrogenated rosin and tall oil. Specifically, in this embodiment, the weight ratio of coumarone resin, hydrogenated rosin and tall oil is 1:0.9:0.5, that is, the addition amount of coumarone resin is 5 kg, the addition amount of hydrogenated rosin is 4.5 kg, and the addition amount of tall oil is 2.5 kg.

[0101] [Example 8]

[0102] A highly elastic rubber, which differs from [Example 7] in that the antioxidant is different.

[0103] The antioxidant includes a mixed compound of antioxidant BLE and antioxidant 4020. Specifically, in this embodiment, the mixing weight ratio of antioxidant BLE and antioxidant 4020 is 1:2, that is, the added amount of antioxidant BLE is 1.2 kg, and the added amount of antioxidant 4020 is 2.4 kg.

[0104] Comparative Example

[0105] [Comparative Example 1]

[0106] A rubber, which differs from [Example 1] in that no thermoplastic starch particles and starch-coated modified silica are added.

[0107] [Comparative Example 2]

[0108] A rubber, which differs from [Example 1] in that the thermoplastic starch particles are replaced by an equal amount of starch.

[0109] [Comparative Example 3]

[0110] A rubber, which differs from [Example 1] in that an equal amount of white carbon black is used to replace the starch-coated modified white carbon black.

[0111] Performance test data

[0112] 1. Rebound resilience test: refer to "GB / T 1681-2009 Determination of rebound resilience of vulcanized rubber" for testing, and record the rebound rate (%) of the vulcanized rubber prepared in each embodiment and comparative example.

[0113] 2. Mooney viscosity test: refer to GB / T 1232.1-2016 Determination of unvulcanized rubber by disc shear viscometer Part 1: Determination of Mooney viscosity" to test the second rubber material (i.e., mixed rubber) in the preparation process of each embodiment and comparative example, and record the Mooney viscosity (50ML (3+4) 100°C) of the unvulcanized second rubber material in the preparation process of each embodiment and comparative example.

[0114] 3. Tensile strength test: refer to GB / T 528-2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber, and record the tensile strength (MPa) of the vulcanized rubber prepared in each embodiment and comparative example and the tensile stress (MPa) when stretched to 500%, wherein the stretching speed is 500 mm / min.

[0115] 4. Hot air accelerated aging: The vulcanized rubber prepared in each embodiment and comparative example was placed in an oven at 100° C. and baked for 72 h. The tensile strength test was then performed again, and the tensile strength (MPa) of the vulcanized rubber after heat aging was recorded.

[0116] Table 1 Rubber performance test data

[0117]

[0118] Combining Example 1 with Comparative Examples 1-3 and the data in Table 1, it can be seen that by adding thermoplastic starch particles and starch-coated modified white carbon black to the rubber system formula mainly based on cis-1,4-dimethyl-1-butadiene rubber, although the rebound resilience of the vulcanized rubber will be slightly reduced, the tensile strength and anti-aging performance of the vulcanized rubber can be greatly improved, making its mechanical properties better. At the same time, the thermoplastic starch particles and starch-coated modified white carbon black combined with plasticizers can effectively improve the Mooney viscosity of the mixed rubber, thereby overcoming the shortcomings of poor adhesion, poor agglomeration, and low processing performance of cis-1,4-dimethyl-1-butadiene rubber, which is conducive to making the mixed rubber fully stick to the roller during the mixing process and improving the processing performance of the mixed rubber.

[0119] Specifically, by comparing the preparation methods and test data of Example 1 and Comparative Example 2, it can be seen that after replacing the thermoplastic starch particles with ordinary starch, the Mooney viscosity of the rubber mix is ​​greatly improved, while the tensile strength and heat aging resistance of the vulcanized rubber are reduced. This may be because ordinary starch does not have the good reinforcing effect of thermoplastic starch if it has not been plasticized and modified, and because ordinary starch has a low melting point, it may be burned and gelatinized under high-temperature mixing, and further increase the Mooney viscosity of the rubber mix, which may cause the rubber mix to stick to the roller excessively, resulting in poor fluidity of the rubber mix and reduced processing performance.

[0120] Secondly, it can be seen from the preparation methods and test data of Comparative Example 1 and Comparative Example 3 that after replacing the starch-coated modified silica with ordinary silica, although the tensile strength of the vulcanized rubber only shows a small decrease, the decrease in the tensile strength of the vulcanized rubber after accelerated aging with hot air increases significantly. This may be because the starch-coated modified silica is cross-linked by the reaction of the hydroxyl and aldehyde groups on the surface of ordinary starch with the silane groups on the surface of silica, and a starch-based covering layer is formed on the surface of silica after cross-linking, and the starch molecules coated on the surface not only improve the overall thermal resistance of silica, but also improve the compatibility of silica in the non-polar rubber system, so that it can be evenly distributed in the mixed rubber and fully combined with the rubber system. Compared with ordinary silica, the starch-coated modified silica can better improve the thermal stability and mechanical strength of the vulcanized rubber.

[0121] Combining Example 1 with Example 3 and the data in Table 1, it can be seen that when the proportion of thermoplastic starch particles in the rubber mix decreases and the proportion of starch-coated modified silica increases, the Mooney viscosity of the rubber mix shows a slight decrease, while the tensile strength and modulus of the vulcanized rubber show an increase, which means that compared with thermoplastic starch particles, starch-coated modified silica has a better reinforcement effect and can more intuitively improve the mechanical strength of the vulcanized rubber.

[0122] In combination with Example 1 and Example 4-7 and in combination with the data of Table 1, when coumarone resin, hydrogenated rosin and tall oil are used in plasticizers according to 1: (0.9-1.2): (0.2-0.5) mixing weight ratio mixing, although the mechanical strength of the vulcanized rubber is not as high as the vulcanized rubber obtained when selecting coumarone resin and hydrogenated petroleum, or coumarone resin, hydrogenated petroleum and aromatic oil three kinds of mixed compounding, the heat aging resistance is also relatively poor, but the overall mechanical properties are not much different, in an acceptable range, and the vulcanized rubber resilience and processing properties are better. And as the proportion of hydrogenated rosin in the rubber system decreases and the proportion of tall oil increases, the resilience of the vulcanized rubber can be further improved, the tensile stress decreases, and the mechanical strength decreases not much, that is, it is explained that the vulcanized rubber at this time has high elasticity while also having good mechanical strength, and the overall performance is better.

[0123] Combining Example 7 and Example 8 with the data in Table 1, it can be seen that when the antioxidant is selected from antioxidant BLE and antioxidant 4020 and compounded at a mixing weight ratio of 1:2.5, the obtained vulcanized rubber has better heat aging resistance than when antioxidant 4020 is used alone.

[0124] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by patent law as long as they are within the scope of the claims of the present application.

Claims

1. A highly elastic rubber, characterized in that: It includes the following raw materials in parts by weight: Natural rubber: 15-30 parts; Butadiene rubber: 45-50 parts; Solution polymerized styrene butadiene rubber: 25-35 parts; Thermoplastic starch granules: 5-10 parts; Starch coated modified white carbon black: 35-40 parts; Stearic acid: 2-3 parts; Zinc oxide: 3-5 parts; Plasticizer: 10-12 parts; Vulcanization accelerator: 2.8-3.2 parts; Sulfur: 0.2-0.5 parts; Dicumyl peroxide: 0.8-1.2 parts; Carbon black: 3-5 parts; Silane coupling agent Si75: 4-6 parts; Anti-aging agent: 2.8-3.6 parts; The thermoplastic starch particles are prepared by modifying starch with a composite plasticizer, and the composite plasticizer is a mixture of formamide, sorbitol and urea; The plasticizer is a mixture of coumarone resin, hydrogenated rosin and tall oil in a weight ratio of 1:(0.9-1.2):(0.2-0.5); the vulcanization accelerator is a mixture of N-cyclohexyl-2-benzothiazole sulfonamide and N,N'-dithiocaprolactam in a weight ratio of 1:(0.4-0.6).

2. The high elastic rubber according to claim 1, characterized in that: The preparation method of the thermoplastic starch granules comprises the following steps: Corn starch and water are stirred and mixed in a weight ratio of 1: (1-1.5), and then a composite plasticizer is added, wherein the mixing weight ratio of the corn starch to the composite plasticizer is 1: (0.2-0.25), the mixture is kept at room temperature and fully stirred at a speed of 2500-3000 r / min, and then allowed to stand for 24-48 hours, and then heated, melted, extruded, cooled, granulated, and fully crushed and ground to obtain thermoplastic starch particles.

3. A highly elastic rubber according to claim 2, characterized in that: In the composite plasticizer, the mixing weight ratio of the formamide, the sorbitol and the urea is 1:(1-1.2):(0.8-1.2).

4. The high elastic rubber according to claim 1, characterized in that: The preparation method of the starch-coated modified white carbon black comprises the following steps: First, corn starch and water are fully stirred in a weight ratio of 1: (8-10), and the mixture is heated to 62-65° C. and stirred for 2-3 hours. After forming a paste, fumed silica is added, wherein the mixing weight ratio of the silica to the corn starch is 1: (0.15-0.2). The mixture is heated to 84-86° C. and stirred for 1-2 hours. The moisture is then dried and the mixture is fully crushed to obtain starch-coated modified silica.

5. The high elastic rubber according to claim 1, characterized in that: The antioxidant includes one or a combination of antioxidant BLE and antioxidant 4020.

6. The high elastic rubber according to claim 5, characterized in that: The antioxidant is a mixture of the antioxidant BLE and the antioxidant 4020, and the mixing weight ratio of the antioxidant BLE to the antioxidant 4020 is 1:(2-2.5).

7. A method for preparing a highly elastic rubber according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, firstly, the solution polymerized styrene-butadiene rubber is placed alone at 86-92° C. for kneading for 2-3 minutes, then the thermoplastic starch particles and the starch-coated modified white carbon black are added, and the kneading is continued for 2-3 minutes before the rubber is discharged to obtain a first rubber compound; S2, placing the natural rubber and the butadiene rubber at 138-145° C. for banburying for 2-3 min, then adding the zinc oxide, the stearic acid, the silane coupling agent Si75, the carbon black and 50% of the first rubber compound, continuing banburying for 2-3 min, then adding the plasticizer, the antioxidant and the remaining first rubber compound again, continuing banburying for 2-3 min, to obtain a second rubber compound; S3, heating the second rubber material to 150-160° C., and adding the vulcanization accelerator, the sulfur and the dicumyl peroxide at the same time, and continuing to mix for 15-20 minutes. After the rubber is discharged, the rubber is pressed into sheets and cooled to obtain a high elastic rubber.

Citation Information

Patent Citations

  • Method for preparing starch / white carbon black composite fillers

    CN103881420A

  • Process for preparing starch-reinforced rubber and use in tyre thereof

    CN1251374A

  • Rubber composition for tire tread

    JP2005002287A